Quality Of Public Service Performance Using The Balance Scorecard Method In The Population And Civil Registration Office Of Cianjur District - Fauziah, Giani Nur; Maruapey, Muhammad Husein; Aprilliyani, Neng Virly (MultiTech Publisher, 2024)
The performance of public sector organisations can be evaluated by measuring both financial and non-financial aspects using the Balanced Scorecard method. The research method employed in this study is quantitative, utilising data collection techniques through literature review, observation, questionnaires, interviews, and documentation. The number of samples used was 100 individuals, with a sample size of 26. The data analysis employed in this study utilises Likert data obtained from observations in the field. The responses were then processed according to the respondents' answers through the use of questionnaires or surveys, using the Weight Mean Score (WMS) formula. The significance of this research lies in its potential to improve the services of the Population and Civil Registration Office of Cianjur Regency in terms of managing KTP-el to the community. This can be achieved by improving the quality of services provided and the facilities and infrastructure available. Ultimately, this will ensure that individuals do not experience any difficulties or inconveniences when accessing services related to population administration.